(untitled) (Docentes 2.0 Journal, 2021)
The world is immersed in a digital revolution; consequently, it is going through a phase of transformation impacting different areas of knowledge, including education, a discipline forced to offer pertinent responses to a set of demands resulting from a constantly changing context. Personal Learning Environments (PLE) constitute a pedagogical approach aimed at using the potential to improve learning. The present essay proposed an approach to knowledge of the PLE; from a review of its main foundations, it was based on documentary research through archiving information combined with content analysis. The results show that PLEs facilitate learning by integrating different contexts thanks to the combination of tools and applications; they are a way to explore different approaches to pedagogy by adapting educational systems to the dynamics imposed by society’s knowledge. Therefore, higher education institutions need to assume the commitment to direct efforts to shape ecosystems that cross the boundaries between formal and informal, opening opportunities for flexible education, capable of harmoniously combining both environments.